2015
DOI: 10.1186/s12865-015-0128-6
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis secretory proteins downregulate T cell activation by interfering with proximal and downstream T cell signalling events

Abstract: BackgroundMycobacterium tuberculosis (M. tuberculosis) modulates host immune response, mainly T cell responses for its own survival leading to disease or latent infection. The molecules and mechanisms utilized to accomplish immune subversion by M. tuberculosis are not fully understood. Understanding the molecular mechanism of T cell response to M. tuberculosis is important for development of efficacious vaccine against TB.MethodsHere, we investigated effect of M. tuberculosis antigens Ag85A and ESAT-6 on T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Accordingly, we observed elevated levels of IL-17A in subjects carrying the AA genotype as compared to individuals that carry the GG genotype, both in plasma and in supernatants of in vitro stimulated PBMC, and independently of the population analyzed. Thus, NFAT might be involved in this differential synthesis of IL-17A, given that this transcription factor promotes the transcription of genes during T lymphocyte activation and was detected in cells stimulated with Mtb antigens304344. However, further studies are required to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, we observed elevated levels of IL-17A in subjects carrying the AA genotype as compared to individuals that carry the GG genotype, both in plasma and in supernatants of in vitro stimulated PBMC, and independently of the population analyzed. Thus, NFAT might be involved in this differential synthesis of IL-17A, given that this transcription factor promotes the transcription of genes during T lymphocyte activation and was detected in cells stimulated with Mtb antigens304344. However, further studies are required to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 98%
“…ESAT-6/ESAT-6:CFP-10 manipulates many host factors in macrophage and hijacks the host immune system to make a safe niche for the bacilli to survive inside the macrophages. It has been reported earlier that ESAT-6 plays a crucial role in supporting intracellular growth of the bacilli in host (5,7,(39)(40)(41)(42)(43)(44). In the previous study, we have demonstrated that ESAT-6 alone or in complex with CFP-10 (ESAT-6:CFP-10) interacts with b2M, and the C-terminal end of ESAT-6 is crucial for its interaction with b2M as ESAT-6 protein with deletion of 6 aa in the C-terminal end failed to interact with b2M (10).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to develop alternative novel methods of adjuvant therapy for TB infections have focused on determining the characteristics of the changes in immune function that occur during TB infection and their risk factors. Consensus has emerged that Mtb downregulates the activation of CD4 T-cells through secreted-protein-mediated interference with T-cell proximal and downstream signals, leading to Th1/Th2 imbalance [ 3 ] and eventually inducing low expression of CD4 [ 4 , 5 ]. However, reports on the changes in CD8 T-cells have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%